The role of exercise-induced myokines in promoting angiogenesis - Qi, Chao; Song, Xianjing; Wang, He; Yan, Youyou; Liu, Bin (Frontiers in Physiology, 2022)
Ischemic diseases are a major cause of mortality or disability in the clinic. Surgical or medical treatment often has poor effect on patients with tissue and organ ischemia caused by diffuse stenoses. Promoting angiogenesis is undoubtedly an effective method to improve perfusion in ischemic tissues and organs. Although many animal or clinical studies tried to use stem cell transplantation, gene therapy, or cytokines to promote angiogenesis, these methods could not be widely applied in the clinic due to their inconsistent experimental results. However, exercise rehabilitation has been written into many authoritative guidelines in the treatment of ischemic diseases. The function of exercise in promoting angiogenesis relies on the regulation of blood glucose and lipids, as well as cytokines that secreted by skeletal muscle, which are termed as myokines, during exercise. Myokines, such as interleukin-6 (IL-6), chemokine ligand (CXCL) family proteins, irisin, follistatin-like protein 1 (FSTL1), and insulin-like growth factor-1 (IGF-1), have been found to be closely related to the expression and function of angiogenesis-related factors and angiogenesis in both animal and clinical experiments, suggesting that myokines may become a new molecular target to promote angiogenesis and treat ischemic diseases. The aim of this review is to show current research progress regarding the mechanism how exercise and exercise-induced myokines promote angiogenesis. In addition, the limitation and prospect of researches on the roles of exercise-induced myokines in angiogenesis are also discussed. We hope this review could provide theoretical basis for the future mechanism studies and the development of new strategies for treating ischemic diseases.